Metode Umum dan Khusus dalam Tafsir Fi Zhilal Al-Qur’an Karya Sayyid Qutub - Nana Najatul Huda; Siti Pajriah (Jurnal Iman dan Spiritualitas, 2022)
This revelation in the form of the Qur'an is shown to people with different circumstances and worldviews. So it is possible and even necessary for the emergence of various kinds of interpretation. And it is essential to adjust between classical interpretations and the current events. Departing from that, Sayyid Qutub made the door for the latest convenience in interpreting the Koran which departs from the reality of society and straightens out what is considered untrue that occurs in that reality by creating a method of writing interpretation that is characteristic of his interpretation by Sayyid Qutub is very much needed in the study of interpretation. This research is qualitative through literature review. This study aims to discuss general methods and specific methods in the interpretation of the fi zhilal Qur'an by Sayyid Qutub. This research discusses general methods and special methods or characteristics used by Sayyid Qutub in interpreting the Koran and sources of interpretation that are al-iqtirani. This research concludes that. Tafsir fi Zhilal al-Qur'an which is the work of this Sayyid breathes movement. This interpretation is in the form of tahlili and at the same time has its own characteristics in the method of interpretation, one of which emphasizes something that is considered important and related to human behavior, eliminates misinterpretations that grow in the world, finally tries to explain how the verse is applied in society.